The Ideological Ambiguity of Internet Art: Vaporwave, Yugowave and Serbwave - Tisa Jukić (INSAM)
This paper concerns the recent internet-based music genre of yugowave. I first analyze the relation of this genre to its original Western model, vaporwave. Differences between the two, in terms of subject matter, ideology, and aesthetics are discussed, along with the complex question of the memory of the SFRY and Yugonostalgia in yugowave. Introducing serbwave as a relation of yugowave, the encounter in praxis between the in theory politically neutral genre of vaporwave and propaganda is also discussed. Finally, I offer two possible readings of serbwave: either as one of several current neo-nationalistic appropriations of the vaporwave aesthetic, or, possibly, a way of processing cultural trauma caused by the wars of the 1990s.